Endometrial cancer in Ibadan: epidemiological and clinico-pathological features -10 year review (2016)
Endometrial cancer is the commonest cancer of the female genital tract, it accounted for about 6 percent of all female cancers in United States. It is not as common in Africa; it was the third commonest gynaecological malignancy in an African study. The aim was to enumerate the characteristics of endometrial cancer patients: socio demographic characteristic of the endometrial cancer patients, and the association of the patients’ profile with endometrial cancer. This was a retrospective, cross sectional study of histologically diagnosed endometrial cancers at the University College Hospital (UCH), Ibadan. The data obtained were analyzed using SPSS. Endometrial cancer accounted for 3.1% of the female genital cancers; Obesity was a factor in most the patients; Poorly differentiated adenocarcinoma was the commonest observed pattern. Majority of the patients were elderly obese, they never engaged in contraception.